2019
DOI: 10.1074/jbc.rev118.002811
|View full text |Cite
|
Sign up to set email alerts
|

Chaperome heterogeneity and its implications for cancer study and treatment

Abstract: The chaperome is the collection of proteins in the cell that carry out molecular chaperoning functions. Changes in the interaction strength between chaperome proteins lead to an assembly that is functionally and structurally distinct from each constituent member. In this review, we discuss the epichaperome, the cellular network that forms when the chaperome components of distinct chaperome machineries come together as stable, functionally integrated, multimeric complexes. In tumors, maintenance of the epichape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 136 publications
2
53
0
Order By: Relevance
“…Interestingly, the clearest differentiation of HSP content was seen for distribution of inducible HSP70-1/2; while abundant in HEK293T, PSMs were not detected in equivalent eHSP of U87. Differentiation in HSP70 isoform representation may reflect specific features of tumorigenic phenotype and genetic stability, as recently determined by Chiosis group (Wang et al 2019). HSP60 was prominent in U87 and choriocarcinoma HELA and may be ratiometric of invasive phenotype (Caruso Bavisotto et al 2018) and inflammatory response (Kato and Svensson 2015).…”
Section: Proteomic Analysismentioning
confidence: 68%
See 2 more Smart Citations
“…Interestingly, the clearest differentiation of HSP content was seen for distribution of inducible HSP70-1/2; while abundant in HEK293T, PSMs were not detected in equivalent eHSP of U87. Differentiation in HSP70 isoform representation may reflect specific features of tumorigenic phenotype and genetic stability, as recently determined by Chiosis group (Wang et al 2019). HSP60 was prominent in U87 and choriocarcinoma HELA and may be ratiometric of invasive phenotype (Caruso Bavisotto et al 2018) and inflammatory response (Kato and Svensson 2015).…”
Section: Proteomic Analysismentioning
confidence: 68%
“…Therefore, any opportunity to collect multiple secreted biomarkers afforded by robust HSP affinity enrichment is significant for translation to targeted clinical assays (Diamandis 2012). With regard to cumulative significance of extracellular HSP, in a survey of over 200 cancer cell cultures and primary isolates, Chiosis' group found that genetic stress rather than acute toxin treatment induced the most dramatic change in HSP profile as a stress-specific fingerprint (Wang et al 2019). For example, under toxic stress, HSP60 was recruited to the HSP90 chaperome network while genetic stress enlisted HSP70 isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor avidity can be a diagnostic imaging biomarker of the molecular target to which the drug tracer binds in vivo. Tumor avidity for the isotopologue I-124 PU-H71 is a well-credentialed imaging biomarker of tumor epichaperome formations [ 49 , 68 ]. Epichaperomes are hyperconnected, integrated functional networks of chaperome units, induced by cellular stress as associated with malignancy [ 49 , 68 , 69 , 70 ].…”
Section: What Does Tumor Signal On a Drug Tracer Image Signify?mentioning
confidence: 99%
“…In this context, specifically in higher organisms, given co-chaperones are able to load specific clients on Hsp90, modulating its activity in different cell tissues or along particular pathways [3]. Hsp90 and its co-chaperone systems are particularly overexpressed in transformed cells associated to disease states, especially cancer and neurodegeneration [4][5][6].…”
Section: Introductionmentioning
confidence: 99%